Cyclic cohesive zone model damage parameter acquisition for fatigue crack growth considering crack closure effect. (October 2022) - Wang, Rongqiao; Liu, Yu; Mao, Jianxing; Liu, Zonghui; Hu, Dianyin
Highlights: Development of the damage evolution equation that takes into account the inhomogeneity of damage distribution at the crack tip. CCZM damage parameter acquisition method based on crack closure experiments. Establishment of a cyclic jump algorithm considering damage rate in fatigue damage evolution. Abstract: This paper presents a method to obtain damage parameters for cyclic cohesive zone model based on the crack closure experiments. The damage evolution is modified by introducing equivalent separation to quantify the nonuniform damage distribution along the crack path. The damage parameters acquisition is realized with digital image correlation analysis, where the effect of crack closure is accordingly elaborated. An adaptive cycle jump technique is established based on the damage rate, aiming to reduce the computational cost. Compared with the experimental data, the proposed model exhibits the capability in predicting fatigue crack growth rate.